2017
DOI: 10.21010/ajtcam.vi15.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithic Activity of Berberis Trifoliata Extract on Induced Urolithiasis in Rats by Zinc Disc Implantation

Abstract: Background:In clinical therapy, there is no satisfactory drug available for treatment of urolithiasis, especially for the prevention of their recurrence. The aim of this work was to evaluate in vivo antiurolithic activity of methanolic extract of Berberis trifoliata leaves. Material and methods: Urolithiasis was induced in Wistar rats by zinc disc implantation in urinary bladder. Upon postsurgical recovery, different doses of the methanolic extract of B. trifoliata leaves (50, 100 and 150 mg/kg body weight) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This study showed that the oral administration of different concentrations of extract (50, 100, and 150 mg/kg) for 20 days decreased the formation and the weight of the dry stones removed from the urinary bladder compared with the control group. Furthermore, this study showed that intervention with methanolic extract of B. trifoliata promoted a significant reduction in the crystal depositions in a model of UL induced by the implantation of a zinc disc in the bladder [ 40 ].…”
Section: Plants Used In Mexican Traditional Medicine Against Urolithi...mentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that the oral administration of different concentrations of extract (50, 100, and 150 mg/kg) for 20 days decreased the formation and the weight of the dry stones removed from the urinary bladder compared with the control group. Furthermore, this study showed that intervention with methanolic extract of B. trifoliata promoted a significant reduction in the crystal depositions in a model of UL induced by the implantation of a zinc disc in the bladder [ 40 ].…”
Section: Plants Used In Mexican Traditional Medicine Against Urolithi...mentioning
confidence: 99%
“…These beneficial effects could be associated with the presence of anthocyanins and alkaloid compounds, mainly berberine. This compound has been identified as a component responsible for potential therapeutic effects, including an anti-urolithiatic effect [ 40 , 41 ].…”
Section: Plants Used In Mexican Traditional Medicine Against Urolithi...mentioning
confidence: 99%
See 1 more Smart Citation